Analytical delay models for signalized intersection - Čelar Nikola Đ. (Tehnika, 2014)
Delay, defined as the additional travel time, is a main indicator of the quality of traffic process at the signalized intersection and important input parameter in the traffic signal settings. Delay value can be determined by using non-experimental (analytical and simulation) and experimental methods. Analytical models provide a fast and simple procedure for their determination. This paper presents the result of comparing the delay values obtained using the relevant analytical models and the real values measured at the field. It was concluded, that none of the analyzed models do not fully estimated the real delay values, and that the minimum deviation is obtained by using HCM 2010. delay model.